Studies on eugenia palembanica (myrtaceae) - Wong, Janet Pik Ching. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Eugenia palembanica plant from the Myrtaceae family was studied in order to know some of its chemical components and the cytotoxicity level on the brine shrimps, Artemia salina. Extraction with cyc1ohexane, chloroform and ethanol solvent gave 0.94 g (0.94%),0.96 g (0.96%) and 4.80 g (4.80%) crude extract respectively. The crude sample of cyc1ohexane, chloroform and ethanol gave 3, 8 and 7 spots on the Thin Layer Chromatography plate (TLC). Most of the fractionated compound in the present study shows the presence of carbonyl group and an almost pure compound is suspected to be of chalcone because of the bright yellow spot on TLC plate and showed the presences of carbonyl group analyzed by Fourier Transformed Infrared Spectrometer and flavonoid pattern in Ultra Violet Visible Spectrometer. A very low cytotoxicity with Artemia salina was observed for all the crude extracts.